1978
DOI: 10.1002/1097-0142(197806)41:6<2388::aid-cncr2820410643>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tests and Hodgkin's disease.A standardized approach to their evaluation

Abstract: We have analyzed a series of 124 young men with Hodgkin's Disease in an attempt to clarify the role of non-invasive tests in the staging evaluation. Data are presented in a way which permits comparison between series and application of the data to decision-making models. Analysis of the data shows our patients to have had primarily limited (stage I and 11) disease. In our hands certain tests were quite accurate in predicting the absence of abdominal disease (lymphangiography, hepatic scintigraphy) as determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For the detection of hepatic involvement in the malignant lymphomas, 5NT is more reliable and has been reported by one group to be more accurate for the diagnosis of metastatic liver disease than liver scanning.24 A more recent report, in which radiological data from four centers were summarized, showed that hepatic scintigraphy correlated poorly with results of laparotomy in detecting hepatic involvement in patients with Hodgkin's Disease. 20 Other authors found an unsatisfactory correlation between baseline liver tests, liver biopsy results, and the clinical course of patients with Hodgkin's Disease (predominantly Stage 1-11) followed up for a minimum period of four years, but the biochemical tests employed were restricted to aminotransferases, Alp, bilirubin, and bromosulphalein clearance ,21 moreover, the methods and reference ranges were not described in their report. As shown in Table 5, 14 cases with initial or subsequent hepatic involvement gave abnormal serum 5NT activities, whereas detection rates for the other four enzymes ranged from 7-9.…”
Section: Discussionmentioning
confidence: 98%
“…For the detection of hepatic involvement in the malignant lymphomas, 5NT is more reliable and has been reported by one group to be more accurate for the diagnosis of metastatic liver disease than liver scanning.24 A more recent report, in which radiological data from four centers were summarized, showed that hepatic scintigraphy correlated poorly with results of laparotomy in detecting hepatic involvement in patients with Hodgkin's Disease. 20 Other authors found an unsatisfactory correlation between baseline liver tests, liver biopsy results, and the clinical course of patients with Hodgkin's Disease (predominantly Stage 1-11) followed up for a minimum period of four years, but the biochemical tests employed were restricted to aminotransferases, Alp, bilirubin, and bromosulphalein clearance ,21 moreover, the methods and reference ranges were not described in their report. As shown in Table 5, 14 cases with initial or subsequent hepatic involvement gave abnormal serum 5NT activities, whereas detection rates for the other four enzymes ranged from 7-9.…”
Section: Discussionmentioning
confidence: 98%
“…Harris et al [19] analyzed 124 lymphangiograms from Walter Reed Hospital and found the predictive value of a positive test to be 36%, and negative tests had a predictive value of 91%. This is equivalent to the terms accuracy positive/negative used in this report.…”
Section: Discussionmentioning
confidence: 99%